Breastfeeding
1 online resource
Keywords: "Breastfeeding: New Anthropological Approaches" unites sociocultural, archaeological and biological anthropological scholarship to spark new trans-disciplinary conversations and research about breastfeeding. While breastfeeding has become the subject of intense debate in many settings, anthropological perspectives have played a limited role in these conversations. The present volume seeks to broaden the scope of discussion on breastfeeding by showcasing fresh insights gleaned using an array of theoretical and methodological approaches in the close study of human groups across the globe. Drawing on case studies and analyses of key issues in the field, the book highlights the power of anthropological research to illuminate the evolutionary, historical, biological, and cultural context of the complex, lived experience of breastfeeding. By bringing together a group of researchers across three anthropological subfields, the volume seeks to stimulate intellectual exchange and new thinking about breastfeeding in order to produce transformative knowledge about human lactation, breastfeeding, and human milk.This book is a key resource for scholars of medical and biological anthropology, evolutionary biology, social and cultural anthropology, and studies in human development. Practitioners (including midwives and lactation consultants) who must fulfil an anthropology requirement as part of their training will also find the book an essential read. "--Provided by publisher.